An exploratory study identifying where local government public health decision makers source their evidence for policy - Stoneham, Melissa; Dodds, J. (Australian Health Promotion Association, 2014)
Issue addressed: The Western Australian (WA) Public Health Bill will replace the antiquated Health Act 1911. One of the proposed clauses of the Bill requires all WA local governments to develop a Public Health Plan. The Bill states that Public Health Plans should be based on evidence from all levels, including national and statewide priorities, community needs, local statistical evidence, and stakeholder data. Methods: This exploratory study, which targeted 533 WA local government officers, aimed to identify the sources of evidence used to generate the list of public health risks to be included in local government Public Health Plans. Results: The top four sources identified for informing local policy were: observation of the consequences of the risks in the local community (24.5%), statewide evidence (17.6%), local evidence (17.6%) and coverage in local media (16.2%). Conclusions: This study confirms that both hard and soft data are used to inform policy decisions at the local level. Therefore, the challenge that this study has highlighted is in the definition or constitution of evidence. So what?: Evidence is critical to the process of sound policy development. This study highlights issues associated with what actually constitutes evidence in the policy development process at the local government level. With the exception of those who work in an extremely narrow field, it is difficult for local government officers, whose role includes policymaking, to read the vast amount of information that has been published in their area of expertise. For those who are committed to the notion of evidence-based policymaking, as advocated within the WA Public Health Bill, this presents a considerable challenge.